Temporal Profile and Limb-specificity of Phasic Pain-Evoked Changes in Motor Excitability. (21st August 2018) - Algoet, M.; Duque, J.; Iannetti, G.D.; Mouraux, A.
Highlights: Phasic pain induces an early-latency increase of motor responses in flexor muscles of the stimulated hand. A later reduction of motor excitability is observed in hand flexor and extensor muscles. In the non-stimulated limb, a prolonged motor facilitation is observed possibly specific for nociception. Abstract: A fundamental function of nociception is to trigger defensive motor responses to threatening events. Here, we explored the effects of phasic pain on the motor excitability of ipsilateral and contralateral arms. We reasoned that the occurrence of a short-lasting nociceptive stimulus should result in a specific modulation of motor excitability for muscles involved in the withdrawal of the stimulated limb. This was assessed using transcranial magnetic stimulation (TMS) of the left and right primary motor cortex to elicit motor-evoked potentials (MEPs) in three flexor and two extensor muscles of both arms. To assess the time-course of nociception-motor interactions, TMS pulses were triggered 50–2000 ms after delivering short-lasting nociceptive laser stimuli to the left or right hand. We made three main observations. First, nociceptive stimuli induced an early-latency (100 ms) enhancement of MEPs in flexor muscles of the stimulated hand. Considering its latency, this modulation is likely consequent to nociceptive-motor interactions at spinal level. This early and lateralized enhancement was followed by a later (150–400 ms) MEP reduction in extensor muscles of the stimulated hand and flexor muscles of both hands, predominant at the stimulated hand. Finally, we observed a long-lasting (600–2000 ms) MEP enhancement in muscles of the non-stimulated hand. These later effects of the nociceptive stimulus could reflect nociception-motor interactions occurring at cortical level.